Pola Kemitraan Petani Padi Beras Merah Organik dengan PT. Sirtanio Organik Indonesia di Kabupaten Banyuwangi - Fariz Irzat Arifin; Triana Dewi Hapsari (UPT Penerbitan Universitas Jember, 2018)
The organic farming system aims to produce agricultural healter without chemical residues and reduce soil, water and air pollution. PT. Sirtanio Organik Indonesia is a private company engaged in organic agriculture that produces organic red rice as a best seller product of the company. His business produces organic red rice, PT. Sirtanio Organik Indonesia has partnered with organic red rice farmers with a system of employment contracts that applies to only one planting season so that organic red rice farmers need to do a period of work contract expansions. The existence of the employment contract causes the number of partners of organic red rice partners every planting season is not the same. The research objective was to identify partnership patterns between organic rice farmers and partner companies. The research area was determined purposively and the problems were answered using descriptive methods. From the results of the study, it is known that to become a partner farmer, the farmer must fulfill several conditions determined by the partner company. The partnership pattern between farmers of PT. Sirtanio Organik Indonesia with organic red rice farmers is a sub-contract partnership pattern which is characterized by rice cultivated by partner rice farmers which is the main ingredient by partner companies to produce organic brown rice.